Effect of Ball-to-Powder Ratio on Morphology, Structure, and Flowability of Ball-Milled Gray Cast Iron Powder - Zhao, Ze-Wen; Shao, Xiang-Yang; Wang, Ke; Wang, Qiang; Xing, Ya-Zhe (Journal of thermal spray technology, 2021)
With the conventional gas or water atomization process of synthesizing metallic powders, it is difficult to obtain graphite structure in a gray cast powder particle because of rapid cooling of the molten droplets. In this work, a fabrication method of gray cast iron powder with graphite structure was proposed based on a structural transplantation route. In the fabrication process, the precursor powder was firstly prepared by mechanically separating from as-cast gray cast iron bulk, then the precursor powder was ball-milled with different ratios of ball-to-powder to obtain final powders. The profile, size distribution, and surface roughness of final powders were quantitatively characterized by circularity, particle uniformity level, and fractal dimension method, respectively. It was found that ball milling smoothed the sharp edges and corners of the precursor powder and reduced the size of the precursor powder. As a result, the ball-milled powders have a more regular shape, more uniform size distribution, lower surface roughness, and better flowability than the precursor powder for thermal spray applications.